Improving Utilisation and awareness of Family Planning services in Adults of Reproductive age through Community Sensitization in Police Wing Village, Jinja District. - Isiko, Henry Rodgers; Kato, Charles; Okumu, Jeremiah; Babita, Mariam; Kumakech, Jacob; Lakisa, Mercy Faith; Isabirye, Hamza; Nambuba, Shanny (Student’s Journal of Health Research Africa, 2021)
Background Family planning refers to a conscious effort by a couple to space the number of children they have through the use of contraceptive methods. According to WHO, an estimated 225 million women in developing countries, 24.2% of women of reproductive age have an unmet need for contraception. However, contraceptive use in sub-Saharan Africa is low at only 21%. The total fertility rate remains high for many countries in the region (4.6 in Kenya and Rwanda, 5.4 in Tanzania, 6.2 in Uganda, and 6.4 for Burundi). Methodology This was a community-based project implementation on increasing awareness and utilization of family planning methods in Police Wing village, Jinja district. Consent was gotten from the VHT, LC1, and DHO before mobilizing people to gather at the VHT’s home and her neighbor’s compound where we carried out the different educational sessions. Different team members got different roles to play as regards the health education session. One week later, we evaluated the progress of our project implementation through the administration of questionnaires to the same people we health educated. The questionnaire assessed the level of utilization, awareness, myths, misconception, and demography of the participants. Results 28% had heard about at least three family planning methods and 24.1% had at one time used family planning while 75.9% of the participants admitted not to have used it. The post-session assessment showed an increase from 28% to 93% in knowledge regarding the available methods of FP and an increase in the utilization of FP from 28% to 42%. Conclusion and recommendations Addressing the myths and misconceptions about FP by exposing them as a fallacy would help increase the uptake as evidenced by the will of the community to take up the different methods. Organize frequent health talks about FP in the community.